Resummation in QCD Fractional Analytic Perturbation Theory - Bakulev, A.P. (Відділення фізики і астрономії НАН України, 2010)
We describe the generalization of Analytic Perturbation Theory (APT) for QCD observables, initiated by Radyushkin, Krasnikov, Pivovarov, Shirkov, and Solovtsov, to fractional powers of coupling — Fractional APT (FAPT). The basic aspects of FAPT are shortly summarized. We describe how to treat heavy-quark thresholds in FAPT and then show how to resum perturbative series in both the one-loop APT and FAPT. As an application, we consider the FAPT description of the Higgs boson decay Hº → bb¯. The main conclusion is: To achieve an accuracy of the order of 1%, it is enough to consider up to the third correction. Представлено узагальнення аналiтичної теорiї збурень (АТЗ) для КХД-амплiтуд, iнiцiйованої роботами Джонса, Соловцова i Ширкова, на дробовi степенi ефективного заряду – дробово-аналiтична теорiя збурень (ДАТЗ). Обговорено проблему порогiв важких кваркiв в ДАТЗ, пiсля чого показано, як можна пiдсумувати весь пертурбативний ряд в однопетльовiй АТЗ i ДАТЗ. Як додаток розглянуто розрахунок ширини розпаду хiггсiвського бозона Hº → bb¯.